Detection of cervical intraepithelial neoplasia (CIN) by visual inspection of cervix with acetic acid (VIA) and its comparison to cervical cytology (TAJ: Journal of Teachers Association, 2019)
Background: Cervical cancer is the second most common cancer in women throughout the world, and it is the leading cause of cancer death among women in underdeveloped countries like Bangladesh is preventable and curable if detected at and early stage using proper screening tools. This study was done to see the effectiveness of VIA and find out the CIN and introduce as a complementary to cytology for diagnosing precancerous form of cervix.Materials & Methods: A total 175 subjects were studied & relevant data of cervix related patients have been collected. The data regarding Pap smear, VIA and biopsy have been taken and collected data was analysis by SPSS.Results: Out of 175 Patients VIA positive 53 (30.3%), Pap smear reports, 84 (48.0%) had inflammatory findings and 38 (21.7%) had dysplasia and biopsy result 41(23.4%) CIN positive. Sensitivity of VlA was 90.2%, specificity 88.1%, PPV 69.8%, NPV 96.7% and accuracy 88.6%. Sensitivity of Pap smear reports was 80.5%, specificity 96.3%, PPV 86.8%, NPV 94.2% and accuracy 92.6%.Conclusion: Visual inspection of cervix after application of acetic acid (VIA) is valid as cytology test for the identification of pre-invasive cervical cancer (CIN). Thus VIA is a useful screening method of Cervical Intraepithelial Neoplasia lesion as Pap smear.TAJ 2018; 31(1): 15-20